2021
DOI: 10.1016/j.xkme.2021.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Focal Segmental Glomerular Sclerosis and Minimal Change Disease: A Qualitative Study of Children and Adults to Inform Patient-Reported Outcomes

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(36 citation statements)
references
References 25 publications
0
36
0
Order By: Relevance
“…A total of twelve studies were included for review: six published qualitative research studies [ 10 , 11 , 20 23 ]; four written patient testimonial series from a patient advocacy group (Nephcure) [ 24 – 27 ], and two video patient testimonials from a patient advocacy group (Nephcure) [ 28 , 29 ]. The 13 studies explored FSGS ( n = 7) and NS ( n = 6).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of twelve studies were included for review: six published qualitative research studies [ 10 , 11 , 20 23 ]; four written patient testimonial series from a patient advocacy group (Nephcure) [ 24 – 27 ], and two video patient testimonials from a patient advocacy group (Nephcure) [ 28 , 29 ]. The 13 studies explored FSGS ( n = 7) and NS ( n = 6).…”
Section: Resultsmentioning
confidence: 99%
“…The 13 studies explored FSGS ( n = 7) and NS ( n = 6). Six studies included an adult population [ 11 , 21 , 22 , 24 , 25 , 28 ], four studies included a pediatric population [ 23 , 26 , 27 , 29 ], and two studies included both adult and adolescent populations [ 10 , 20 ]. All studies were conducted in the US or Canada.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…36 Griffin described how the profound impact of nephrotic syndrome is seen on the lives of patients in her clinic, and can be especially devastating for children and young adults and during pregnancy. Studies have revealed that the impact includes physical symptoms, such as shortness of breath, severe oedema, and fatigue, 37,38 as well as an increased risk of cardiovascular problems, such as acute coronary syndrome, heart failure, venous thromboembolism, and death. 35 FSGS has also been shown to lead frequently to HRQoL issues such as anxiety, depression, poor sleep, and a reduced ability to socialise.…”
Section: Symposium Reviewmentioning
confidence: 99%